Assessment of plant diversity and associated mycorrizhal fungi in the mined-out sites of atlas mines in Toledo, Coty Cebu for bioremediation - Aggangan, Nelly S. (Journal of Environmental Science and Management, 2015)
The diversity of plant and mycorrhizal fungi within the 35,000-ha of the Atlas Mines in Toledo, Cebu, was surveyed with the goal of rehabilitating their mined-out area through bioremediation (the use of dominant plants and mycorrhizal fungi present in area to contain/reduce pollutants). From five one km transect lines in five sites, the survey indicated that the vegetation was classified as a disturbed grass-shrubland-savanna-agroforest plant community with tree plantations in rehabilitated sites. Plant composition comprised 69 species belonging to 66 genera and 35 families which include trees, shrubs, herbs, creepers, vines, agricultural or agroforest crops. Fruit bodies of ectomycorrhizal fungi (ECMF), namely: Pisolithus, Scleroderma, Thelephora and Boletellus were found under Acacia auriculiformis, A. mangium, Eucalyptus urophylla and E. camaldulensis. Pisolithus were the most dominant. For arbuscular mycorrhizal fungi (AMF), out of 50 plants collected, 10-100% roots of Lycopodium, Saccharum spontaneum, Nephrolepsis, Acacia mangium and Stachytarpheta jamaicensis were colonized by AMF. All roots of S. jamaicensis were colonized solely by Glomus sp. Pithecellobium dulce harboured the highest spore density (2,575 spores/plant/30g dry soil), consisting of Glomus (42%), Acaulospora (24%) and Entrophospora (37%). Muntingia calabura was the only plant associated with Glomus, Gigaspora, Scutellospora, Acaulospora and Entrophospora, though with low spore population. Glomus was the most prevalent among the AMF. The above AMF and ECMF can be mass-produced as biofertilizers for use in bioremediation of mined-out sites and other areas with similar conditions.